Oral desmopressin in neonatal diabetes insipidus. Issue 11 (November 1987) - Stick, S M; Betts, P R
Abstract : A neonate with cranial diabetes insipidus was successfully treated with oral desmopressin. The patient had a midline cleft lip and palate and we obtained a more consistent response using the oral route than using the usual nasal route.